Factors Affecting Personal Financial Management - Syaefa Intan Salsabilla; Naelati Tubastuvi; Purnadi Purnadi; Maulida Nurul Innayah (Universitas Muhammadiyah Yogyakarta, 2022)
Research aims: This study aims to analyze the effect of financial education in the family, financial literacy, peers, and a hedonism lifestyle on personal financial management. Design/Methodology/Approach: Based on Roscoe's calculations, 100 respondents were sampled. The results of the analysis show that financial education in the family do not affect students personal financial management. The population in this study were undergraduate students of the Faculty of Economics and Business, University of Muhammadiyah Purwokerto, Jenderal Soedirman University, and State Islamic University of Saifuddin Zuhri class of 2018-2020. The sample selection in this study used a purposive sampling technique. Research findings: The results of the analysis show that financial education in the family do not affect students personal financial management. Meanwhile, financial literacy, peers, and hedonism lifestyle have a positive effect on students personal financial management. Theoritical contribution/Originality: This study uses the theory of planned behavior, which in this theory states that there are three factors that influence this theory, namely 1) attitude towards behavior, 2) subjective norm, and 3) perceived behavioral control. This study gives contribution to manage personal management.Practitioner/Policy implication: Practically, this research implies the importance of managing personal finances so as to avoid consumptive behavior. Research limitation/Implication: Limitations in this study are the results of R2 of 46%, which means that the variables studied are good enough to influence the personal financial management of students and also this research is only in 1 faculty with a sample of 100.